-0.2(x-4)=1.7

Simple and best practice solution for -0.2(x-4)=1.7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -0.2(x-4)=1.7 equation:


Simplifying
-0.2(x + -4) = 1.7

Reorder the terms:
-0.2(-4 + x) = 1.7
(-4 * -0.2 + x * -0.2) = 1.7
(0.8 + -0.2x) = 1.7

Solving
0.8 + -0.2x = 1.7

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-0.8' to each side of the equation.
0.8 + -0.8 + -0.2x = 1.7 + -0.8

Combine like terms: 0.8 + -0.8 = 0.0
0.0 + -0.2x = 1.7 + -0.8
-0.2x = 1.7 + -0.8

Combine like terms: 1.7 + -0.8 = 0.9
-0.2x = 0.9

Divide each side by '-0.2'.
x = -4.5

Simplifying
x = -4.5

See similar equations:

| 5=r/4 | | 2x^6+13x^3-45=0 | | 4(2l+2)=24 | | (-5x+3)+(-4x^2+5x+7)= | | a=2+3b+2c | | (a-3b)(4a^2-6b+4)= | | 5d+5e-2e+6d= | | -2/3x-21=27/4 | | 3(a-5)=39 | | 4x+2=-4+2x+22 | | 5x+24=2x+66 | | -8/9x=-48 | | (q-4)*5=10 | | 32=-8d | | -0.2(x-4)=-1.7 | | 3/4x-1.72=-6.82 | | 8x+17=9x+11 | | y(y+-1)=0 | | 15g-h=6 | | 5x^6+43x^3+56=0 | | a-2=3b+2c | | 4m=3m+14 | | 2xj= | | 6-2x=5x+15 | | 5+4x(2+7)= | | 2x+1.6=8.4 | | 1X+21=5 | | 5+6x=-5x-28 | | 16x^4+8(sqrt(3))x^3-12x^2-8(sqrt(3))x-3=0 | | w(w+2)=52 | | P+3r=15 | | 3(m-1.5)=1.5(2m+3) |

Equations solver categories